2021
DOI: 10.1021/acs.jafc.1c05213
|View full text |Cite
|
Sign up to set email alerts
|

Erythritol Improves Nonalcoholic Fatty Liver Disease by Activating Nrf2 Antioxidant Capacity

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a kind of serious fat disorder that has become a critical problem to human society. Therefore, finding drugs that are safe and effective has become more and more important. Erythritol (Ery) is a polyol sweetener with a variety of biological functions. However, whether Ery has a relieving effect on NAFLD has not been reported yet. Therefore, we induced HepG2 cells with oleic acid and palmitic acid as our in vitro model. Moreover, we choose wild-type mice with tyloxapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Humid conditions were optimized with a CO 2 concentration of 5% to culture HepG2 cells in DMEM with 10% FBS at 37 °C. The cells were subjected to pre-treatment with AT (200 μM) for 1 h and then treated with a certain amount of palmitic acid (PA; 660 μM; Sigma, Missouri) and oleic acid (OA; 330 μM; Sigma, Missouri) for 24 h. PA and OA were dissolved in alcohol prior to their application …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Humid conditions were optimized with a CO 2 concentration of 5% to culture HepG2 cells in DMEM with 10% FBS at 37 °C. The cells were subjected to pre-treatment with AT (200 μM) for 1 h and then treated with a certain amount of palmitic acid (PA; 660 μM; Sigma, Missouri) and oleic acid (OA; 330 μM; Sigma, Missouri) for 24 h. PA and OA were dissolved in alcohol prior to their application …”
Section: Methodsmentioning
confidence: 99%
“…The cells were subjected to pre-treatment with AT (200 μM) for 1 h and then treated with a certain amount of palmitic acid (PA; 660 μM; Sigma, Missouri) and oleic acid (OA; 330 μM; Sigma, Missouri) for 24 h. PA and OA were dissolved in alcohol prior to their application. 19 Cell Counting Kit-8 (CCK8) Assay. The viability of HepG2 cells was detected by employing CCK8 (Saint-Bio, Shanghai, China).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The Nrf2 signaling pathway has been reported to play an antioxidant role in nonalcoholic steatohepatitis [ 24 ], liver fibrosis [ 25 ], and liver ischemia/reperfusion [ 26 ], which may offer a novel potential strategy for the prevention and treatment of liver diseases [ 27 ]. Sulforaphane (SFN), an agonist of Nrf2 that has been demonstrated to promote the nuclear translocation of Nrf2 and suppress oxidative stress [ 28 ], was chosen to verify the protective role of the Nrf2 pathway in TP-induced cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 Nuclear factor erythroid 2-related factor 2 (Nrf2), a nuclear transcription factor, transferred into the nucleus and regulated the expressions of many antioxidant-related proteins such as heme oxygenase 1 (HO-1), glutamyl cysteine ligase, peroxiredoxin, superoxide dismutase, and NAD(P)H quinone dehydrogenase 1 (NQO1). 34,35 The expressions of antioxidant proteins could decrease excessive ROS and alleviate cell death induced by ROS. In addition to the effects of antioxidant proteins on ROS, mitophagy participated in the regulation of ROS levels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These studies demonstrated that excessive ROS participated in the regulation of necroptosis. Organelles of ROS generation in cells include mitochondria, endoplasmic reticulum, and peroxisomes. , Nuclear factor erythroid 2-related factor 2 (Nrf2), a nuclear transcription factor, transferred into the nucleus and regulated the expressions of many antioxidant-related proteins such as heme oxygenase 1 (HO-1), glutamyl cysteine ligase, peroxiredoxin, superoxide dismutase, and NAD­( P )H quinone dehydrogenase 1 (NQO1). , The expressions of antioxidant proteins could decrease excessive ROS and alleviate cell death induced by ROS. In addition to the effects of antioxidant proteins on ROS, mitophagy participated in the regulation of ROS levels. , Damaged mitochondria could be encapsulated and degraded by autophagy, known as mitophagy.…”
Section: Introductionmentioning
confidence: 99%